Development of Articulate Storyline Learning Media to Improve the Writing Ability of French Students - Rabiah Adawi; Evi Eviyanti (Britain International for Academic Research (BIAR) Publisher, 2022)
The purpose of this study is to develop the application of articulate storyline learning media and Production crite lémentaire textbooks to improve the writing skills of students of the French Language Education Study Program, Medan State University. a companion for the explanation of the grammar section from Chapter I to Chapter V so that students can study independently and use the ISBN Production crite lémentaire textbook. The resulting products are in the form of web and applications that can be operated offline on laptops, tablets and smartphones. Another target to be achieved in this research is the published indexed international journals. The research method in this study uses research and development (Research and Development) Borg and Gall consists of ten implementation steps including (1) research and data collection, (2) planning, (3) product draft development, (4) field trials, (5) improvement of initial product, (6) field trial, (7) refinement of product resulting from field test, (8) field implementation test, (9) refinement of final product, and (10) dissemination and implementation. The data needed in this study will be collected through a student needs analysis questionnaire.